GNPTAB c.2404C > T nonsense mutation in a patient with mucolipidosis III alpha/beta: a case report - Chi-Chun Ho; Lilian Li-Yan Tsung; Kam-Tim Liu; Wing-Tat Poon (BMC, 2018)
Abstract Background Mucolipidosis alpha/beta is an inborn error of metabolism characterized by deficiency of GlcNAc-1-phosphotransferase, in which essential alpha/beta subunits are encoded by the GNPTAB gene. The autosomal recessive condition is due to disruptions of hydrolase mannose 6-phosphate marker generation, defective lysosomal targeting and subsequent intracellular accumulation of non-degraded material. Clinical severity depends on residual GlcNAc-1-phosphotransferase activity, which distinguishes between the milder type III disease and the severe, neonatal onset type II disease. Case presentation We report the clinical, biochemical and genetic diagnosis of mucolipidosis III alpha/beta in a two-year-old Chinese boy who initially presented with poor weight gain, microcephaly and increased tone. He was confirmed to harbor the common splice site mutation c.2715 + 1G > A and the nonsense variant c.2404C > T (p.Q802*). Clinically, the patient had multiple phenotypic features typical of mucopolysaccharidosis including joint contractures, coarse facial features, kypho-lordosis, pectus carinatum and umbilical hernia. However, the relatively mild developmental delay compared to severe type I and type II mucopolysaccharidosis and the absence of macrocephaly raised the possibility of the less commonly diagnosed mucolipidosis alpha/beta. Critical roles of lysosomal enzyme activity assay, which showed elevated α-iduronidase, iduronate sulfatase, galactose-6-sulphate sulphatase, arylsulfatase B and α-hexosaminidase activities; and genetic study, which confirmed the parental origin of both mutations, were highlighted. Conclusions The recently reported nonsense variant c.2404C > T in the GNPTAB gene is further recognized and this contributes to the genotype-phenotype spectrum of mucolipidosis alpha/beta.